Spatially Confined Hybridization of Nanometer‐Sized NiFe Hydroxides into Nitrogen‐Doped Graphene Frameworks Leading to Superior Oxygen Evolution Reactivity. (26th June 2015) - Tang, Cheng; Wang, Han‐Sen; Wang, Hao‐Fan; Zhang, Qiang; Tian, Gui‐Li; Nie, Jing‐Qi; Wei, Fei
<x xml:space="preserve">Abstract</x> Nanometer‐sized hydroxide active centers are uniformly and strongly hybridized into a graphene framework by means of defect‐anchored nucleation and spatially confined growth, resulting in a superior electrocatalyst for oxygen evolution reaction. This family of strongly coupled complexes and the topology‐assisted fabrication strategy is expected to open up new avenues of research. It sheds light on a novel branch of advanced nano‐architectured materials.